Nile tilapia culture on domestic effluent treated in stabilization ponds. - Clovis Matheus Pereira; Flavio Rubens Lapolli (Biotemas, 2009)
The performance and filet quality of tilapias (Oreochromis niloticus) culture in effluent stabilization lagoons was tested at the densities of 3 fish/m2 (T3), 7 fish/m2 (T2) and 7 fish/m2 in clean water + diet (T1) with 3 repetitions in tanks of 2.57m2 and 0.60m of water column with supplemental aeration. Fish culture in clean water plus diet (T1) presented the highest growth. The higher density T3 (7/m2) compared to T2 (3/m2) did not result in any difference of total production (p > 0.05) but this was compensated by the increased individual fish growth rate at lower density. The conditions that sustain fish survival culture with ETE effluent were attested by the high survival (> 90%) under both treatments, but only 10% of the water samples from T2 and T3 N-total ammonium was favorable for fish growth (< 2.0mg/L). The rearing system improved the effluent quality, reducing the total organic nitrogen and the solids in suspension. The faecal coliforms, Salmonella sp. and Staphylococcus aureus from the effluent and fish were verified to be within the standards laid down by the World Health Organization (WHO).